Utilization of Galleries as Educational Spaces for Artistic Creation by Students - Esterica Yunianti; Nanang Yulianto (PAEDAGOGIA, 2024)
The art gallery serves as a space for the exhibition of art objects and creations, intended for appreciation. Typically, art galleries are often perceived as uninteresting and monotonous places, appealing only to a select audience.  However, art galleries are not merely exhibition spaces; they can also serve as venues for communication, learning, workshops, discussions, and even artistic creation. Located in Clupak Mojopuro Sumberlawang Sragen, there is a residence that not only serves as a dwelling but also functions as an art gallery known as "Sanggar Rumah Langit Kebun Bumi."This study aims to elucidate the role of the gallery within Sanggar Rumah Langit Kebun Bumi.  Employing qualitative research methods, data were collected through observation and interviews, involving on-site visits to garner information both through direct observation and informant insights. Data were analyzed based on Miles & Huberman's theory, involving data collection, data presentation, data reduction, and verification (Miles, 1992). Data collection was conducted through interviews and observations. Data presentation involved organizing the data into tables to facilitate clear analysis. Data reduction simplified the collected data to align with the study's needs, enabling further elaboration and analysis. In the data verification stage, the researcher ensured accuracy and reliability through data triangulation with various sources. The research activities were conducted within Sanggar Rumah Langit Kebun Bumi, revealing numerous endeavors, primarily exhibitions, while also serving as a platform to foster artistic awareness, notably through painting activities. The painting activities were designed to provide students with an opportunity to develop their knowledge, skills, and gain practical experience, referred to as a Residensi sehari bersama pelajar (One-day Residency with Students). This residency initiative offers students the chance to gain experience in the realm of art, particularly in painting